Stabilization period before capturing an ultra-short vagal index can be shortened to 60 s in endurance athletes and to 90 s in university students - Krejčí, Jakub; Botek, Michal; McKune, Andrew J (PloS one, 2018)
PURPOSE: To find the shortest, acceptable stabilization period before recording resting, supine ultra-short-term Ln RMSSD and heart rate (HR). METHOD: Thirty endurance-trained male athletes (age 24.1 ± 2.3 years, maximal oxygen consumption (VO2max) 64.1 ± 6.6 ml·kg-1·min-1) and 30 male students (age 23.3 ± 1.8 years, VO2max 52.8 ± 5.1 ml·kg-1·min-1) were recruited. Upon awaking at home, resting, supine RR intervals were measured continuously for 10 min using a Polar V800 HR monitor. Ultra-short-term Ln RMSSD and HR values were calculated from 1-min RR interval segments after stabilization periods from 0 to 4 min in 0.5 min increments and were compared with reference values calculated from 5-min segment after 5-min stabilization. Systematic bias and intraclass correlation coefficients (ICC) including 90% confidence intervals (CI) were calculated and magnitude based inference was conducted. RESULTS: The stabilization periods of up to 30 s for athletes and up to 60 s for students showed positive (possibly to most likely) biases for ultra-short-term Ln RMSSD compared with reference values. Stabilization periods of 60 s for athletes and 90 s for students showed trivial biases and ICCs were 0.84; 90% CI 0.72 to 0.91, and 0.88; 0.79 to 0.94, respectively. For HR, biases were trivial and ICCs were 0.93; 0.88 to 0.96, and 0.93; 0.88 to 0.96, respectively. CONCLUSION: The shortest stabilization period required to stabilize Ln RMSSD and HR was set at 60 s for endurance-trained athletes and 90 s for university students.
Keywords: Young Adult; fyzická vytrvalost; studenti; Male; mladý dospělý; nervus vagus; Athletes; sportovci; Heart Rate; mužské pohlaví; srdeční frekvence; Time Factors; lidé; Physical Endurance; Students; Humans; Vagus Nerve; časové faktory; Heart Rate Determination; určení tepové frekvence; Universities; univerzity